Clinical overview of patients submitted to the dosage of specific prostatic antigen (PSA) (Research, Society and Development, 2020)
Prostate specific antigen (PSA) is the main marker for prostatic changes. The increase in PSA in peripheral blood may be age-related, and it is recommended that men over 40 years of age be tested. The aim of the present study is to trace the clinical profile of patients submitted to PSA dosage and to direct the care provided by the health team. This is a descriptive, retrospective study with quantitative approaches, developed with male patients, aged 30 years or older submitted to the PSA dosage test, from January 2017 to December 2018. The results obtained in this study study show that PSA levels increase according to age, and may also be indicative of Benign Prostatic Hyperplasia, thus requiring complementary tests for a reliable diagnosis. It is concluded that patients between 61 and 70 years old have the highest values of total PSA altered, and the “November Blue” campaign did not influence the laboratory routine, showing that the campaign may not be effective in the private network.